Large-area metal surface plasmon–polymer coupled nanocomposite thin film at air–liquid interface for low voltage operated high-performance photodetector - Singh M.K.; Mishra R.; Prakash R.; Yi J.; Heo J.; Pandey R.K. (My University, 2025)
Coupling of metal surface plasmon resonance (SPR) with organic molecules and successive fabrication of large-area films is an effective approach for enhancing photogenerated excitons while retaining their optical thickness. In this regard, we present the facile synthesis of a silver nanoparticle (Ag NP) SPR–polymer coupled large-area nanocomposite thin film (8 ± 0.5-cm-diameter circular film) at the air–liquid interface and the fabrication of a high-performance visible-region photodetector (PD). The formation of nanocomposite films was investigated via multiple techniques, which revealed the formation of an SPR/organic molecule unified system. The photoresponse of the nanocomposite film was examined by fabricating a sandwich-structure ITO/PQT-12-Ag NP/Al Schottky device PD and measuring the photocurrent; responsivity R(λ), which was 9.624 × 104, 3.384 × 104, and 2.372 × 104 mA/W; external quantum efficiency, which was 19.03 × 103, 8.92 × 103, and 5.54 × 103; and detectivity (D), which was 1.06 × 1013, 3.70 × 1012, and 2.60 × 1012 Jones, at a bias voltage of −1.5 V for 627-nm (red), 470-nm (blue), and 530-nm (green) light, respectively. The high performance of the PDs in the visible region was discussed according to the spectral, KPFM, morphological, and energy band diagram results. © 2022 Elsevier B.V.